“Teaching Illustration and Storytelling Techniques in Fine Arts Lessons: Pedagogical Foundations” - Qudratova Gulizuhro Otabek qizi (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article explores pedagogical foundations for teaching illustration and storytelling techniques in fine arts lessons. Integrating visual storytelling enhances students’ creativity, narrative thinking, and ability to convey ideas through art. The study examines methods for teaching narrative composition, character design, sequential art, and illustrative techniques, combining theoretical instruction with practical exercises and modern pedagogical technologies.